Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges: Exploring Opportunities and Challenges (University of Maribor Press, 2025)
The scientific monograph ‘Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges’ addresses current and carefully selected topics in the field of children’s rights. It specifically focuses on issues where the authors critically analyze and discuss the protection of children’s rights in the context of sustainable development and digital transformation, as well as the challenges posed by both environments. The contributors engage in critical discourse and offer in-depth analyses of children’s rights from both substantive and procedural legal perspectives, examining developments at the national level as well as within the international legal framework. They clearly identify inconsistencies, shortcomings, and difficulties that children’s rights face in the context of sustainability and digitalization. In their contributions, the authors emphasize the importance of safeguarding children’s rights in judicial proceedings and highlight the role and responsibilities of both national and international actors in this field. They further discuss selected aspects of children’s vulnerability and violations of their rights, especially in relation to children affected by armed conflict, those living in crisis regions, and children with disabilities, web.